2008
DOI: 10.1007/s11661-007-9398-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal and Isothermal Oxidation Behavior of Nb-Si-Mo Alloys

Abstract: The nonisothermal and isothermal oxidation behavior of arc-melted, hypereutectic ternary alloys have been investigated vis-a`-vis that of Nb and Nb-10Si alloy. The nonisothermal studies carried out using simultaneous thermogravimetric and differential thermal analysis in the temperature range of 50°C to 1300°C using heating rates of 5°C, 15°C/min, 25°C/min, and 40°C/min have shown oxidation initiation at lower temperatures for slower heating rates and higher Mo content. Isothermal oxidation experiments have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
0
27
1
1
Order By: Relevance
“…Comparison of the data given in Table 6 indicates that the oxidation resistance of the NbCrMo 0.5 Ta 0.5 TiZr alloy is much better than that of the Nb-Al, Nb-Si, Nb-Si-Al, and Nb-Si-Al-Ti alloys, as well as Nb-13Si-4Mo and Nb-19Si-5Mo alloys, and similar to that of the Nb-18Si-26Mo alloy. However, oxidation resistance of the developmental Nb-12Si-15Mo alloy [29] is slightly better than that of our alloy.…”
Section: Oxidation Kineticscontrasting
confidence: 60%
See 2 more Smart Citations
“…Comparison of the data given in Table 6 indicates that the oxidation resistance of the NbCrMo 0.5 Ta 0.5 TiZr alloy is much better than that of the Nb-Al, Nb-Si, Nb-Si-Al, and Nb-Si-Al-Ti alloys, as well as Nb-13Si-4Mo and Nb-19Si-5Mo alloys, and similar to that of the Nb-18Si-26Mo alloy. However, oxidation resistance of the developmental Nb-12Si-15Mo alloy [29] is slightly better than that of our alloy.…”
Section: Oxidation Kineticscontrasting
confidence: 60%
“…FA8650-10-5226. Nb-10Si 37 ---- [29] Nb-10.1Si 45 90 170 -- [28] Nb-17.3Al 23 43 65 -- [28] Nb-5Si-9Al 90 160 275 -- [28] Nb-7Si-9Al 69 145 275 -- [28] Nb-8Si-9Al-10Ti ---182 338 [28] Nb-10Si-9Al-10Ti ---95 291 [28] Nb-6Si-11Al-15Ti ---51 167 [28] Nb-8Si-11Al-15Ti ---51 153 [28] Nb-19Si-5Mo 26 53 106 -- [29] Nb-18Si-26Mo 9.7 13.8 19.5 45 - [29] Nb-13Si-4Mo 48 105 166 -- [29] Nb-12Si-15Mo …”
Section: Discussionunclassified
See 1 more Smart Citation
“…Nb-Si-Mo alloys were examined by Chattopadhyay et al [15] The authors determined that the oxidation behavior was controlled at intermediate temperatures by the hypo-, hyper-eutectic character of the alloy as a result of the accelerated oxidation of large volume fractions of (Nb,Mo) 5 lowers porosity and reduces oxygen diffusion and increases the activity of silicon leading to the development of a layer of SiO 2 . A characteristic multilayer oxide scale is developed on samples that consist of dispersed Nb 2 O 5 particles in a borosilicate glass matrix when boron is added.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently found that the addition of Mo increases the oxidation resistance at high temperature. [2] So, it is important to study the interdiffusion in the Nb-Mo system, which will be helpful in designing the alloy for the application. There are some studies available [3][4][5] in the literature; however, significant differences were found in different studies.…”
mentioning
confidence: 99%